KONSTRUKSI REALITAS BERITA KORUPSI MANTAN BUPATI BENGKALIS HERLIYAN SALEH DI HALUAN RIAU DAN METRO RIAU - Yeni Selviera; Chelsy Yesicha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
National News Agency (LKBN) Between is the first news agency Indonesia which was established in 1937. LKBN Antara continues to grow into a public company with a Bureau in each province and manage news portals in every region spread in Indonesia is no exception Riau province, namely LKBN Between Bureau Riau. In 2015 LKBN Antara Riau was awarded as the first best provincial bureau in the news category. Researchers want to know how the news strategy LKBN Between Riau Bureau in the face of competition with online media, and will be described through news tips, news variations to the speed and depth of news.This research is qualitative research with descriptive approach. In this study using the concepts of Strategy, news, online media and media competition. Subjects in this study were selected based on certain considerations of researchers namely Head of Bureau LKBN Antara Riau, Editor, and journalist LKBN Antara Bureau of Riau, then the object of this research is LKBN Between Riau Bureau.Based on research conducted for nine months then know the results of this study. In the results and discussion then LKBN Between Riau Bureau implement strategies peberitaan or news management process to face competition with other online media. The strategy undertaken LKBN Between Riau Bureau the first is the tips in the news by adding news elements 3E + 1N adder 5W + 1H, highlighting variations for light news. Finally, LKBN Between Riau Bureau meet the depth of news equivalent print media and news speed equivalent to other online media.Kata kunci: Strategi Pemberitaan LKBN Antara